A new micropterous species of the genus Sunius Stephens, 1829 from Central Anatolia (Coleoptera: Staphylinidae). Issue 4 (1st October 2020) - Anlaş, Sinan
Abstract : Sunius shavrini sp. n. is described from Ankara province in central Anatolia. While most of the Turkish Sunius species, especially all Turkish endemics are restricted to the mountains of western Anatolia and the Taurus mountains in southern Anatolia, the new species has been found in the northern part of Central Anatolia. Additional records of two species of Sunius are reported from Turkey. The genus is now represented in Turkey by 42 species, 38 of which are endemic to Anatolia. http://www.zoobank.org/urn:lsid:zoobank.org:pub:35FF690D-2CD9-4B22-96CB-1A32F6B9366D